Internet-Based Brief Personalized Feedback Intervention in a Non-Treatment-Seeking Population of Adult Heavy Drinkers: A Randomized Controlled Trial - Hansen, Anders Blædel Gottlieb; Becker, Ulrik; Nielsen, Anette Søgaard; Grønbæk, Morten; Tolstrup, Janne Schurmann; Thygesen, Lau Caspar (JMIR Publications, 2012)
BackgroundInternet-based interventions for heavy drinkers show promising results, but existing research is characterized by few studies in nonstudent adult populations and few comparisons with appropriate control groups. ObjectiveTo test whether a fully automated Internet-based brief personalized feedback intervention and a fully automated Internet-based personalized brief advice intervention in a non-treatment-seeking population of heavy drinkers would result in a reduced alcohol intake. MethodsWe conducted a 3-arm parallel randomized controlled trial in a general population-based sample of heavy drinkers. The 54,157 participants (median age of 58 years) were screened for heavy drinking. Of the 3418 participants who had a weekly alcohol consumption above 14 drinks for women and 21 drinks for men, 1380 (619 women) consented to take part in the trial and were randomly assigned to an Internet-based brief personalized feedback intervention group (normative feedback, n = 476), an Internet-based personalized brief advice intervention group (n = 450), or a nonintervention control group (n = 454). Follow-up after 6 and 12 months included 871 and 1064 participants, respectively, of all groups combined. The outcome measure was self-reported weekly alcohol consumption. We analyzed the data according to the intention-to-treat principle. To examine changes over time and to account for the multiple time measurements, we used a multilevel linear mixed model. To take attrition into account, we used multiple imputation to address missing data. ResultsThe intervention effect of the Internet-based brief personalized feedback intervention, determined as the mean additional difference in changes in alcohol consumption in the Internet-based brief personalized feedback intervention compared with the control group, was -1.8 drinks/week after 6 months and -1.4 drinks/week after 12 months; these effects were nonsignificant (95% confidence interval -4.0 to 0.3 at 6 months, -3.4 to 0.6 at 12 months). The intervention effect of the Internet-based personalized brief advice intervention was -0.5 drinks/week after 6 months and -1.2 drinks/week after 12 months; these effects were nonsignificant (95% confidence interval -2.7 to 1.6 at 6 months, -3.3 to 0.9 at 12 months). ConclusionsIn this randomized controlled trial we found no evidence that an Internet-based brief personalized feedback intervention was effective in reducing drinking in an adult population of heavy drinkers. Trial registrationClinicalTrials.gov NCT00751985; http://clinicaltrials.gov/ct2/show/NCT00751985 (Archived by WebCite at http://www.webcitation.org/68WCRLyaP)